2023
DOI: 10.1007/s00109-023-02370-z
|View full text |Cite
|
Sign up to set email alerts
|

SPP1/osteopontin: a driver of fibrosis and inflammation in degenerative ascending aortic aneurysm?

David Freiholtz,
Otto Bergman,
Sailendra Pradhananga
et al.

Abstract: Degenerative ascending aortic aneurysm (AscAA) is a silent and potentially fatal disease characterized by excessive vascular inflammation and fibrosis. We aimed to characterize the cellular and molecular signature for the fibrotic type of endothelial mesenchymal transition (EndMT) that has previously been described in degenerative AscAA. Patients undergoing elective open-heart surgery for AscAA and/or aortic valve repair were recruited. Gene expression in the intima-media of the ascending aorta was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Interestingly, non-canonical atherosclerotic processes have recently been described in the aneurysmal intima/media of patients with tricuspid aortic valves, signified by a pathological accumulation of macrophages and a disturbed lipid metabolism 5 . In our recent work, we could further enhance these findings by the identification infiltrating CD68+ immune cells expressing Secreted Phosphoprotein 1 that correlated with aortic dimensions and an augmented expression of inflammatory markers 6 . The mechanism enabling immune cells to migrate into to the sub-intimal space to facilitate inflammation initiation remains, however, unknown.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, non-canonical atherosclerotic processes have recently been described in the aneurysmal intima/media of patients with tricuspid aortic valves, signified by a pathological accumulation of macrophages and a disturbed lipid metabolism 5 . In our recent work, we could further enhance these findings by the identification infiltrating CD68+ immune cells expressing Secreted Phosphoprotein 1 that correlated with aortic dimensions and an augmented expression of inflammatory markers 6 . The mechanism enabling immune cells to migrate into to the sub-intimal space to facilitate inflammation initiation remains, however, unknown.…”
Section: Introductionmentioning
confidence: 83%
“…Indeed, OLR1 mRNA levels correlated with the expression of inflammatory markers, in both dilated and non-dilated aortas, and its expression was co-localized with infiltrating CD68+ cells. Interestingly, innate immune cells are prone to greater inflammatory activation by oxLDL 26 , which in the context of AscAA, may exacerbate downstream immune cell-associated degeneration 6 . Furthermore, a subcluster of OLR1+ macrophages were recently demonstrated in dissecting aortic tissue, that promoted formation of neutrophil extracellular traps 27 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 Previous research has linked SPP1 to abdominal and thoracic aneurysmal illness by upregulating matrix proteinases via NF-B, increasing tissue degradation. 36 , 37 A previous study showed that individuals with abdominal aortic aneurysm and AD had higher levels of SPP1 expression in the plasma and aortic wall than healthy controls. In AD patients, serum SPP1 levels correlate positively with MMP-2 levels.…”
Section: Discussionmentioning
confidence: 99%